Effect of Certain Petroleum Products on the Shear Strength of Clayey Soils - Hameed Majeed, Adel (Journal of Engineering and Sustainable Development, 2005)
The effect of certain petroleum products on the shear strength characteristics of clayey soils is studied. Kerosene, Gas oil, as well as water, are mixed with different types of soils (kaolinite, 80% kaolinite-20% bentonite, and natural clayey soil). Consolidated undrained triaxial tests with pore pressure measurement have been conducted to investigate the effect of these products on the shear strength of the soils studied. The results show a distinct effect of petroleum products on the shear strength characteristics of clayey soils. The shear strength of clayey soils increased with a decrease in the dielectric constant of the pore medium.